1996
DOI: 10.1111/j.1365-2559.1996.tb01401.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary spinal epidural manifestation of malignant lymphoma

Abstract: The clinical, histological and immunomorphological data in 19 cases of primary spinal epidural manifestation of malignant lymphomas collected between 1974 and 1994 are reported. The age of the patients varied between 11 and 87 years with a mean age of 56.3 years. There was a slight male predominance (11:8). In most cases, the onset of the clinical symptoms was rapid. The preferential tumour localization was the epidural space related to the thoracal vertebral bone. In each case, decompressive laminectomy was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…A male preponderance of 69%, which was similar to other studies, was observed. Patients clinically present most commonly in the fifth to seventh decade of life[1518] with more than 80% being older than 40 years. [1141619] Pediatric patients with PSEL, however, have also been reported.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…A male preponderance of 69%, which was similar to other studies, was observed. Patients clinically present most commonly in the fifth to seventh decade of life[1518] with more than 80% being older than 40 years. [1141619] Pediatric patients with PSEL, however, have also been reported.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…This has been attributed to both the greater length of the thoracic spine (compared with the cervical and lumbar) and to an enhanced ability to accommodate bulky disease in the thorax and abdomen. [11314161825] The rich venous plexus in the thoracic spine may be the reason for frequent occurrence of lymphomas in this site. [21]…”
Section: Locationmentioning
confidence: 99%
See 2 more Smart Citations
“…Schwechheimer et al found an increased incidence of B-cell high-grade lymphomas in 11 of 19 cases, centroblastic lymphomas being the predominant type. Of signifi cant note, no signifi cant survival implications were based on histopathological classifi cation ( 14 ).…”
mentioning
confidence: 99%